EFFECT OF DIRECT MARKETING STRATEGY IN STIMULATING CONSUMER PURCHASE: A CASE STUDY IN THE IRAQI CENTRAL MARKETS GENERAL COMPANY - Bushra Jawad M. Ridha (Scholar Express Journals, 2023)
This research seeks to diagnose direct marketing strategy (direct mail, telemarketing, and catalogs) that are appropriate to encourage Consumer Buying decisions for the company’s products and services, and for the purpose of testing research hypotheses, the General Company for Central Markets was selected in the Iraqi Ministry of Trade Company and analyzing the results using the SPSS application. The study reached a number of results, including the company in question to rely on the marketing databases that it provides through market research that it conducts in the process of targeting the consumer audience, and made a set of recommendations, the most important of which are modern direct marketing strategy as bridges that connect the company to its consumers Without an intermediary, it needs continuous development to improve marketing performance and gain the company the advantage of attracting and consumers.
Keywords: consumer buying; direct marketing; direct mail; telephone marketing